Sistem Informasi Pembayaran Pembelian Rumah Berbasis Web Pada PT Dinamika Bersama - Yusron, Faisal; Wicaksono, Harjunadi (JURNAL MAHASISWA BINA INSANI, 2023)
Information System for Down Payment Property at PT Dinamika Bersama with Prototype Methode. Information system is a system that provides information for management decision-making and operational operations of a combination of people, information technology and organized procedures or information systems are defined as a combination of information technology and activities of people who use technology to support operations and management. The research was conducted through stages of observation and interviews from companies. The method used in this research is the Prototype method. This method is applied to the consumer advance payment information system which was originally using the manual method and will be developed using the web. Web-based for down payments make it easier for administrator or end user to input data and minimize data loss